Metodologi Muslim Progresif dalam Memahami Pesan Sejati Al-Qur'an - Mukhlis Mukhlis (IAIN Ponorogo, 2011)
Al-Quran is interpreted in different ways and approaches. Progressive Muslims, for instance, pay attention to three themes, namely social justice, gender equality, and pluralism. They propose their arguments based on the fundamental understading from (alHijr/15:29, Şād/38:71, and al-Nahl/16:90), namely: (1) every human being has the same intrinsic glory, (2) the main mission of human presence in the world is to fight for and uphold justice for all mankind, and (3) human being must be doing good deeds and behave politely. Their approaches are: (a) critical engagement against the tradition, (b) multiple critique on modernity, c) a plurality of sources, and (d) self-positioning, beyond apologetics. Progressive Muslims have a hope to eliminate the uncertainty dilemma of Muslims, i.e between bound by tradition, and the need for responsive with the modernity.